Divergent N Deficiency-Dependent Senescence and Transcriptome Response in Developmentally Old and Young Brassica napus Leaves - Safavi-Rizi, Vajiheh; Franzaring, Jürgen; Fangmeier, Andreas; Kunze, Reinhard (Frontiers in Plant Science, 2018)
In the spring oilseed rape (OSR) cultivar ‘Mozart’ grown under optimal N supply (NO) or mild N deficiency (NL) the transcriptome changes associated with progressing age until early senescence in developmentally old lower canopy leaves (leaf #4) and younger higher canopy leaves (leaf #8) were investigated. Twelve weeks old NO and NL plants appeared phenotypically and transcriptomically identical, but thereafter distinct nutrition-dependent differences in gene expression patterns in lower and upper canopy leaves emerged. In NO leaves #4 of 14-week-old compared to 13-week-old plants, ∼600 genes were up- or downregulated, whereas in NL leaves #4 ∼3000 genes were up- or downregulated. In contrast, in 15-week-old compared to 13-week-old upper canopy leaves #8 more genes were up- or downregulated in optimally N-supplied plants (∼2000 genes) than in N-depleted plants (∼750 genes). This opposing effect of N depletion on gene regulation was even more prominent among photosynthesis-related genes (PSGs). Between week 13 and 14 in leaves #4, 99 of 110 PSGs were downregulated in NL plants, but none in NO plants. In contrast, from weeks 13 to 16 in leaves #8 of NL plants only 11 PSGs were downregulated in comparison to 66 PSGs in NO plants. Different effects of N depletion in lower versus upper canopy leaves were also apparent in upregulation of autophagy genes and NAC transcription factors. More than half of the regulated NAC and WRKY transcription factor, autophagy and protease genes were specifically regulated in NL leaves #4 or NO leaves #8 and thus may contribute to differences in senescence and nutrient mobilization in these leaves. We suggest that in N-deficient plants the upper leaves retain their N resources longer than in amply fertilized plants and remobilize them only after shedding of the lower leaves.